(untitled) (Research, Society and Development, 2024)
Objective: to reinforce the importance and impact that nutrition has under oncology, aiming to present its role in controlling the imbalances of these patients affected by the disease, and the attempt to mitigate the side effects of treatment under their organism. Method: The present study is a systematic literature review. The search was for articles that answer the guide question "Can nutritional therapy contribute to the improvement and/or maintenance of the nutritional status of cancer patients?". Results: Nine articles were selected, two seek to bring an analysis between the adequacy of the prescribed volume and the infusion received by the patient and the impact on the patient’s health status, one seeks to evaluate the importance of the frequency of nutritional counseling in cancer patients, another aims to analyze the impact of enteral and parenteral nutritional therapy on reducing the rate of deaths from neoplasms. One of them discusses the importance of an early initiation of nutritional therapy, in addition to detailing oral immunonutrition therapy in preoperative patients. Conclusion: nutritional therapy is of great importance for the development of positive clinical outcomes in neoplastic patients.